2013
DOI: 10.1200/jco.2012.44.5031
|View full text |Cite
|
Sign up to set email alerts
|

Sex Is an Independent Prognostic Indicator for Survival and Relapse/Progression-Free Survival in Metastasized Stage III to IV Melanoma: A Pooled Analysis of Five European Organisation for Research and Treatment of Cancer Randomized Controlled Trials

Abstract: The persistent independent female advantage, even after metastasis to lymph nodes and distant sites, contradicts theories about sex behavioral differences as an explanation for this phenomenon. A biologic sex trait seems to profoundly influence melanoma progression and survival, even in advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
139
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(152 citation statements)
references
References 31 publications
12
139
0
1
Order By: Relevance
“…Also after adjusting for tumour thickness, Clark's level of invasion and tumour ulceration, women had a 30% lower risk of CMM-related death than men. This superior non-stage effect for women has previously been found in studies with similar HR (19,20). Surprisingly, sex was not included in the final prognostic model in two of the largest published prognostic instruments based on AJCC data and from Queensland Australia respectively (3,4).…”
Section: Discussionmentioning
confidence: 59%
“…Also after adjusting for tumour thickness, Clark's level of invasion and tumour ulceration, women had a 30% lower risk of CMM-related death than men. This superior non-stage effect for women has previously been found in studies with similar HR (19,20). Surprisingly, sex was not included in the final prognostic model in two of the largest published prognostic instruments based on AJCC data and from Queensland Australia respectively (3,4).…”
Section: Discussionmentioning
confidence: 59%
“…In a subsequent study on stage I/II melanoma, it was observed that men had worse prognostic characteristics at diagnosis, and they retained a progression disadvantage of ~30% after diagnosis (7). In 2013, the same group analyzed survival differences across sexes in stage III and IV melanoma patients (8). They again demonstrated the continuity of independent female survival advantage following adjustment for known prognostic factors, despite lymph node and distant metastasis.…”
Section: Univariate Analyses Multivariate Analyses ------------------mentioning
confidence: 88%
“…The first hypothesis was controverted and the second hypothesis was advocated by the fact that the female survival advantage persisted even following adjustment for factors such as Breslow's thickness, and that lymph node and visceral organ metastases did not affect the higher survival rate of female patients (4,(5)(6)(7)(8)(9)(10)(11). Thus, it was concluded that the aggressiveness of the disease did not affect the survival benefit of female melanoma patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an acute need for new therapeutic strategies that augment the efficacy of standard-of-care immune checkpoint inhibitors. Clues to potential new therapeutic targets for melanoma may be found in 50 year old observations (White, 1959), validated in recent studies, that female sex, history of multiple pregnancies, and decreased maternal age at first birth are associated with decreased melanoma incidence and favorable prognosis (Bannister-Tyrrell et al, 2015;Gandini et al, 2011;Hersey et al, 1977;Joosse et al, 2013;Karagas et al, 2006;Magnus, 1977). Although the mechanism of this protective effect is unknown, the clinical association suggests that sex hormone signaling is involved.…”
Section: Introductionmentioning
confidence: 94%